Knowledge and Experience of the Banjar Community in Overcoming Fevers Based on Culture and Health - Hardiyanti, Diana; Heryyanoor, Heryyanoor; Pertiwi, Melinda Restu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Fever is a health problem that needs to be appropriately handled; mishandling fever, especially in children, will have fatal consequences. Various alternatives for treating fever include applying complementary therapies and actions that contain cultural elements such as data, massage, giving coconut oil and shallots, and wind removal. This research describes the knowledge and experience of the Banjar community in dealing with cultural and health-based fever. This type of research is descriptive of the population of the Banjar district community and is taken using a random sampling technique. The sample was 68 respondents, taking into account the inclusion criteria, variables of knowledge, and experience of the Banjar community in dealing with fever. Data was collected using a questionnaire containing 28 knowledge questions and 11 experience statements. Descriptive analysis uses a computer program presented with a frequency distribution table. The knowledge of the Banjar community in dealing with fever was in a suitable category at 95.6%, while the Banjar community's experience in dealing with fever well was only 51.5%. Aspects of public knowledge in dealing with fever include knowledge in handling fever at home is good at 88.2%, understanding and causes of fever are good at 79.4%, managing fever at health services is good at 75%, signs and symptoms of fever are good at only 60.3%, and good fever classification was only 32.4%. The knowledge and experience of the Banjar community in dealing with fever is generally in the excellent category.